Adhesion and biocides inactivation of Salmonella on stainless steel and polyethylene - Tondo, Eduardo Cesar (2014)
The adhesion of Salmonella (S) strains to stainless steel and polyethylene and their inactivation by biocides used in food industry was investigated. Coupons of stainless steel and polyethylene were immersed in bacterial suspensions of S. Enteritidis,S.Typhimurium, and S. Bredeney during 15, 30, and 60 minutes, and submitted to different concentrations of peracetic acid (PAA), sodium hypochlorite (NaOCl), and quaternary ammonium(Quat) sanitizers. Hydrophobicity of the surfaces was evaluated by contact angle measurements using the sessile drop method and bacterial adhesion was accompanied through bacterial counts and scanning electron microscopy(SEM). Results indicated that the three serovars of Salmonella presented similar adhesion to both materials (5.0 to 6.5 log cfu cm-2). The time of exposure did not influence the counts of adhered cells on both surfaces, however SEM revealed larger clusters of S. Enteritidis on both materials, not found for the other serovars. S. Enteritidis presented lower sessile drop angle on polyethylene, indicating hydrophilic properties of this material. The biocides were not able to inactivate all the microorganisms adhered on both surfaces. At least 1 log cfu cm-2 of all serovars tested remained viable after the exposure to different biocide concentrations. In general, higher counts of survivors were observed on polyethylene disinfected with different concentrations of biocides. S. Bredeney e S. Typhimurium were more resistant than S. Enteritidis to PAA, whilst S. Enteritidis presented smaller reduction rates to NaOCl.This last biocide was able to reduce Salmonella counts in approximately 3.0 to 4.0 log cm-2. When adhered to polyethylene, the serovars S. Typhimurium and S. Enteritidis were more resistant to Quat than S. Bredeney in all concentrations tested, and the numbers of S. Enteritidis remained almost unaltered. On stainless steel disinfected by Quat, S. Bredeney presented high numbers of survivors.